Validity Test Of The Foot And Ankle Outcomes Questionnaire as a Measurement Tool For Flat Foot - Inayah, Rizqi Nurul; Waspada, Edy; Wulandari, Enny (Poltekkes Kemenkes Riau, 2024)
The Foot and Ankle Outcomes Questionnaire (FAOQ) assesses disability in the foot and ankle across five areas: pain, symptoms, daily activities, sports and leisure, and quality of life. This study, conducted in 2020, aimed to validate the FAOQ for measuring flat foot in 12-year-old children. Nineteen children with flat feet from Al Abidin Islamic Middle School in Banyuanyar, Surakarta, participated, selected through purposive sampling and Clark's Angle footprint analysis. Each participant provided written consent. The study utilized the FAOQ and Clark's Angle footprint analysis to test the validity of the Indonesian FAOQ version using the Pearson Product Moment. Out of 25 questions, 16 were found invalid and 9 valid. With a table value of 0.482 and a margin of error of 0.05, the FAOQ is deemed valid if the table value exceeds the calculated value. Thus, the Indonesian FAOQ version is invalid for assessing flat foot in 12-year-old children.